2014
DOI: 10.4103/0970-0358.146578
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lymphangiogenesis in acellular dermal matrix

Abstract: Introduction:Much attention has been directed towards understanding the phenomena of angiogenesis and lymphangiogenesis in wound healing. Thanks to the manifold dermal substitute available nowadays, wound treatment has improved greatly. Many studies have been published about angiogenesis and cell invasion in INTEGRA®. On the other hand, the development of the lymphatic network in acellular dermal matrix (ADM) is a more obscure matter. In this article, we aim to characterize the different phases of host cell in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…They engineered a human lymphatic vascular network, which successfully inosculated to the host lymphatic system after transplantation into nude rats. However, so far there is only limited knowledge about lymphangiogenesis within implanted Integra (Cherubino et al, 2014). We found that only a few lymphatic vessels had grown into nonseeded Integra 14 days after implantation.…”
Section: Discussionmentioning
confidence: 74%
“…They engineered a human lymphatic vascular network, which successfully inosculated to the host lymphatic system after transplantation into nude rats. However, so far there is only limited knowledge about lymphangiogenesis within implanted Integra (Cherubino et al, 2014). We found that only a few lymphatic vessels had grown into nonseeded Integra 14 days after implantation.…”
Section: Discussionmentioning
confidence: 74%
“…Lymphatic vessels developed even at the end of the observed period. Similarly, Cherubino et al 14 describes lymphangiogenesis in ADM in rats. However, it should be emphasized that the processes of angiogenesis and lymphangiogenesis is different in rats, and it is apparently faster than in larger animals or in humans.…”
Section: Discussionmentioning
confidence: 90%
“… 7 Much less is known about the processes of integration and subsequent morphological changes in the ADM implanted into host tissues, such as re-cellularization and re-vascularization. Until now, the histology of ADM host tissue integration has been studied in various animal models, including mice, 12 rats, 13 , 14 rabbits, 15 and pigs. 16 , 17 Similar histological studies of human ADM implants are limited, and only one article on this topic has been published by Bullocks.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the dermal substitute (i.e., Integra, Inc., Plainsboro, N.J.) can assist in protecting the pedicle at the same time providing a more pliable skin and a higher vascularity of the reconstructed soft tissues. 19 21 In the present case series, we used the dermal substitute in 3 cases with encouraging results (Table 1 ; Figs. 5 , 6 ).…”
Section: Discussionmentioning
confidence: 62%